Revitalization of Teba Space Design to Preserve Cultural and Environmental Sustainability in Traditional Balinese Houses - Kusuma Putra, I Gusti Ngurah Bagus; Nutrisia Dewi, Ni Made Emmi (International Journal of Engineering, Science and Information Technology, 2024)
Teba, being an essential component of traditional Balinese dwellings, holds a significant role in community assignments, historical and societal contexts of Balinese culture, and ecological sustainability. Nevertheless, the process of urbanization and shifts in lifestyle have resulted in a decrease in Teba spaces and their conversion into less ecologically sustainable regions. This article explores initiatives to rejuvenate the design of Teba spaces in traditional Balinese houses to uphold a harmonious coexistence between environmental and cultural conservation in contemporary times. This research explores techniques and design solutions for Teba places that can effectively adapt to evolving circumstances while upholding traditional values. By doing so, it seeks to promote both environmental and cultural sustainability. This study employs a qualitative and ethnographic methodology to investigate ways for revitalization. These strategies involve the utilization of natural and local materials, the implementation of sustainable design techniques, and the creation of flexible and multifunctional spatial arrangements. The findings suggest that the restoration of Teba contributes to preserving biodiversity and enhancing air quality, reinforces cultural identity, and promotes sustainable tourism development. Integrating traditional techniques with modern technologies can optimize the functionality of Teba as both a productive green area and a center for cultural preservation. Hence, cooperation among architects, government entities, and the community is crucial in developing inventive and sustainable design solutions that enhance the cultural heritage of Bali within evolving circumstances.